(untitled) (Journal of Education and Development, 2023)
The racialised legacies of colonisation in many parts of the globe, have resulted in intergenerational disparities for disproportionate numbers of Indigenous learners and their families. Global responses for indigenous and other minoritised learners have seen the use of culturally responsive pedagogies and theory-based school reform initiatives to better understand the „core‟ changes that are required. In this paper, we bring theory-based, secondary-school reform and culturally responsive pedagogies together in pursuit of equity, excellence and belonging as Māori, for these marginalised learners in Aotearoa New Zealand. We discuss the collaborative building of a pedagogical continuum by teachers. This continuum introduces teachers to the theoretical underpinnings of cultural relationships and responsive pedagogy. Evidence gathered using classroom walkthrough observations is then compared to the continuum in order to understand what is happening with teaching and learning across the school. Surveys used with teachers, students and whānau groups provide further evidence of how they experience classroom pedagogy. Taken together, this evidence is then used to establish more equitable and iterative learning pathways going forward.